Representasi Budaya Batak Dalam Film “Ngeri-Ngeri Sedap” Karya Bene Dion Rajagukguk - Aurillia, Tasya; Supriadi , Supriadi (DIGICOM : Jurnal Komunikasi dan Media, 2024)
Movies are not only entertainment for society, but they also often address and present social issues within society. Films convey social and cultural realities to the public in their daily lives. Sometimes, movies also contain criticisms related to social issues surrounding the community, indirectly enhancing the audience's understanding of events in society. One of the films that tackles social and cultural issues is "Ngeri-Ngeri Sedap," directed by Bene Dion Rajagukguk. This film depicts the life of a Batak family experiencing disruption, or a change in cultural values. This research employs a descriptive qualitative approach and utilizes John Fiske's semiotic analysis to understand the representation of Batak culture, particularly regarding the changes in cultural values undertaken by Domu, Gabe, and Sahat. This analysis involves three levels: the level of reality, representation, and ideology. The findings of this study are categorized into three levels as well. Firstly, at the level of reality, there are 17 scenes indicating shifts in cultural values. These changes include alterations in marriage customs, shifts in career aspirations, and the abandonment of traditions that required the youngest child to care for their parents. At the level of representation, the researched scenes predominantly employ medium close-up camera techniques to convey emotional depth and facial expressions in each scene. This approach aims to delve into each moment of the film. Additionally, the absence of background music emphasizes the dialogues and adds a sense of realism. Natural sounds, particularly those of water or rivers, represent the origin of the Batak Toba tribe, living along the shores of Lake Toba. Lastly, the level of ideology reveals a shift in Batak cultural values towards modernization. Characters like Gabe, Domu, and Sahat view culture as something that no longer needs to be strictly adhered to. As long as they perceive their actions as reasonable, they are willing to deviate from tradition. Especially considering that Domu, Gabe, and Sahat have been living away from their homeland since childhood, their cultural values and perspectives have naturally evolved.